Prosecuting international crimes: a multidisciplinary approach - Krzan, Bartłomiej (Queen Mary studies in international law, 2016)
Individual responsibility and collective state responsibility for international crimes : separate or complementary concepts under international law? / Joachim Wolf -- Customary international law as a basis of an individual criminal responsibility / Wladyslaw Czaplinski -- Immunities before international criminal courts / Robert Uerpmann-Wittzack -- The attribution of international criminal responsibility for serious violations of human rights and international humanitarian law to senior leaders / Krzysztof Maslo -- Crimes against civilians during armed conflicts / Patrycja Grzebyk -- Remedying torturous effects of the use of chemical weapons under international law / Regina Valutyte and Neringa Mickeviciute -- The judicial independence of judges within international criminal courts / Witold Jakimko -- Human rights and international criminal law / Bartlomiej Krzan -- The prosecutor of the International Criminal Court : inquistorial or adversarial? / Karolina Kremens -- Admissibility of illegally obtained evidence in proceedings before international criminal courts / Wojciech Jasinski -- Implementing the Nuremberg principles in national trials with nazi criminals : hesitation versus enthusiasm towards meeting the standards of complementarity in the modern international criminal law / David Kohout -- Sufficient domestic proceedings : the standard of national criminal proceedings before the ICC in context of Art. 17 of the Rome Statute / Karolina Wierczynska -- The South African truth and reconciliation commission in the context of xenophobia, cycles of violence, and epigenetic trauma / Loammi Wolf -- Prosecuting international crimes in Lithuania : when wounds shape the law / Justinas Zilinskas